2012
DOI: 10.1017/s1074070800000146
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Willingness to Pay for Fair Trade Coffee: A Chinese Case Study

Abstract: Coffee consumption in China has seen a significant rise in recent years. This study seeks to explore the determinants of coffee consumption in China with a specific focus on fair trade coffee. In a survey of 564 respondents in Wuhan City, consumers' willingness to pay (WTP) for fair trade labeled coffee was measured. This study uses an interval regression to investigate individual demographic and consumption characteristic impacts on WTP. Results show that on average, consumers were willing to pay 22% more for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 17 publications
9
60
1
2
Order By: Relevance
“…Specifically, the framework is designed for the food sector and encompasses issues that affect the whole supply chain. Accordingly, the framework embraces and extends certain issues, such as fair trade (Loureiro and Lotade 2005;Yang et al 2012), environment-friendly products (Rousseau and Vranken 2013), and animal welfare (Hartmann et al 2013;Liljenstolpe 2008), which have been addressed by previous scholars.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the framework is designed for the food sector and encompasses issues that affect the whole supply chain. Accordingly, the framework embraces and extends certain issues, such as fair trade (Loureiro and Lotade 2005;Yang et al 2012), environment-friendly products (Rousseau and Vranken 2013), and animal welfare (Hartmann et al 2013;Liljenstolpe 2008), which have been addressed by previous scholars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while most of the studies on sustainable certified coffee focused only on Fair Trade (Cicia et al, 2010;de Ferran and Grunert, 2007;De Pelsmacker et al, 2005a;Hainmueller et al, 2015;Koppel and Schulze, 2013;Rotaris and Danielis, 2011;Schollenberg, 2012;Yang et al, 2012Yang et al, , 2013, or eco-friendly (Sörqvist et al, 2013), only a few have assessed the consumer trade-offs between Fair Trade and other sustainability labels such as Organic (Basu and Hicks, 2008;Cranfield et al, 2010;De Pelsmacker et al, 2005b;Langen, 2011), or shade grown coffee (Loureiro and Lotade, 2005). These studies found that Fair Trade coffee was generally preferred over Organic coffee by consumers in Belgium (De Pelsmacker et al, 2005b), Germany (Basu and Hicks, 2008) and the US (Basu and Hicks, 2008;Loureiro and Lotade, 2005).…”
Section: Sustainability Labels On Coffee: An Overviewmentioning
confidence: 99%
“…This result is given further credence by the results of Nelson et al [44], which show that in unequal economic contexts, FT certification benefits the larger producers more than the smaller ones. As shown by Yang et al [26], the guaranteed price under the FT system is often not sustained, and many small farmers in particular may end up indebted, rather than boosting their incomes. During our interviews, local experts in the Kagera region claimed that many small farmers in the study area have taken loans at high interest rates, hampering their ability make repayments and hence negatively affecting their income from coffee production.…”
Section: Analysis Of Farmers' Motivations For Ft Coffee Certificationmentioning
confidence: 99%
“…First, the majority of existing studies examine FT from the perspective of developed-country consumers, by focusing on consumer willingness to pay for FT-certified products [24][25][26] and their ethical buying behavior, including the determinants of buying environmental friendly and fairly traded products [27,28]. However, little is known about small coffee farmers' motivations for FT certification, as very few empirical studies have examined how various factors affect the probability of FT certification, in SSA countries in particular [21,28].…”
Section: Introductionmentioning
confidence: 99%